Stabilization of Traffic Flow Based on the Multiple Information of Preceding Cars (Communications in Computational Physics, 2008)
To enhance the stability of traffic flow, a new car-following model is proposed by taking into account the support of intelligent transportation system (ITS)information, which includes both the headway and the velocity difference of multiplepreceding cars. The new model is based on the Optimal Velocity (OV) model and itsextended models. The stability condition of the model is obtained by using the linearstability theory. Through nonlinear analysis, the modified Korteweg-de Vries equationis constructed and solved, and the traffic flow is classified into three types, i.e. stable,metastable, and unstable. The jam phase can thus be described by the kink-antikinksoliton solution for the mKdV equation. The numerical simulation results show thatcompared with previous models considering only one of the ITS information, the proposed model can suppress traffic jams more efficiently when both headway and velocity difference of arbitrary preceding cars are taken into account. The results of numerical simulation coincide with the theoretical ones.